Unbearable trauma and irreparable damage: maternal death by suicide raises serious perplexities - Dias e Almeida, Kayo Resende; Oliveira, Séphora Natércia Albuquerque; Rolim Neto, Modesto Leite (Avanços em Medicina, 2025)
IntroductionMaternal death by suicide raises serious perplexities. The ICD-10 classifies maternal suicide as an indirect form of maternal death. Due to this current misclassification, a classificatory consensus of maternal suicide as a direct form of maternal death is urgent.ObjectiveAnalyze the psychological  that permeate the phenomenon of maternal suicide, to define the profile of mothers in the postpartum period and pregnant women who commit suicide, with the purpose of elucidating ways of preventing maternal suicide.MethodsA systematic review was made following the PRISMA protocol (Preferred Reporting Items for Systematic Reviews and Meta-Analysis).ResultsTwenty-one studies reported the urgent need to implement interventions in order to prevent or reduce mental health problems caused by mothers and pregnant women who commit suicide. Twenty studies demonstrate the need for interventions to organizational adjustments, especially related to the emotional conflicts involved suicide and maternity.ConclusionMaternal suicide is mainly caused by severe psychiatric disorders, however, higher suicide rates are seen due to psychosocial factors, such as poor familial support and domestic violence, illegal substance abuse and alcoholism, history of sexual or physical violence, racial oppression, economic instability, unwanted pregnancy, difficulty in accessing intentional abortion, and trauma related to past maternity experiences.